Sustainability decision-making in poultry slaughterhouses: A comparative analysis of AHP and fuzzy AHP - Hayati Mukti Asih; Agung Sutrisno; Cynthia E.A. Wuisang; Muhammad Faishal (MethodsX)
The chicken meat industry is vital for global food security and economic growth but faces significant sustainability challenges, especially in balancing economic, environmental, and social aspects. Addressing these challenges in chicken slaughterhouses (CSH) in the Special Region of Yogyakarta, Indonesia, is crucial. This study aims to prioritize criteria for developing strategies to enhance CSH sustainability by comparing the Analytic Hierarchy Process (AHP) and Fuzzy Analytic Hierarchy Process (Fuzzy AHP) using different fuzzy numbers. The findings emphasize the need for a strategy that merges stakeholder engagement, technological innovation, and circular economy principles to advance sustainability. This study fills a research gap by applying multi-criteria decision-making in the poultry industry, which provides a deeper understanding of the robustness and sensitivity of sustainability assessments. • Employing AHP and Fuzzy AHP with different fuzzy numbers enriches sustainability evaluations by balancing precise judgments and expert uncertainties, which enhancing assessment robustness in the poultry industry. • Hygiene and sanitation, market competitiveness, and waste minimization are the three highest priorities for sustainable CSH operations across scenarios. • These findings highlight the need for strategies that integrate stakeholder engagement, innovation, and circular economy principles, addressing a gap in decision-making research for the poultry industry in developing regions.